Qualitative Study on Nutrition- and Health-Related Knowledge Attitudes and Practices in Four High Stunting Regions of Lao PDR - Mbuya, Nkosinathi V.N. (World Bank, Washington, DC, 2020)
Despite the Lao People’s Democratic Republic (Lao PDR)’s significant economic growth over the last decade, poor nutritional outcomes remain a concern. Rates of malnutrition are particularly high in remote, rural, and upland areas. Redressing these high rates of malnutrition is critical in reversing inequalities in mortality and ill-health throughout people’s lives. This report presents the results of a qualitative study to investigate the knowledge, attitudes, and practices related to maternal and child health and nutrition in local communities in four provinces of Lao PDR with high levels of childhood undernutrition. While study participants were aware of the importance and benefits of antenatal care, facility-based birthing, and postnatal care, they also reported significant barriers to accessing these services. These barriers included poor road conditions and lack of transportation, long distances to health facilities, language difficulties, and lack of spousal support. With regard to infant and young child feeding, many mothers were aware of the benefits of colostrum for the first 24 hours and exclusive breastfeeding for the first six months of life and tried to put this into practice. However, some ethnic minority women stated that at times it was hard to prevent grandmothers from giving the infant water or a little chewed rice. There were mixed results when it came to growth monitoring of children. Even though mothers did participate in growth monitoring and promotion activities, most did not fully understand the reasons behind those activities. Access to clean water and appropriate sanitation facilities depended on location, but few families had access to safe water. While messages regarding handwashing and desisting from open defecation were well known in most villages, poverty and lack of support for providing safe and sustainable sanitation systems diminished the ability of many families to practice safe hygienic practices.